1989
DOI: 10.1162/jocn.1989.1.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Aspects of Cortical Somatotopy: A Critical Evaluation

Abstract: The demonstration that functional somatotopic maps within the adult neocortex undergo some degree of reorganization following peripheral injury has aroused considerable interest. The evidence for such reorganization in the rat and monkey is reviewed and it is concluded that in both species there is good evidence for limited functional map reorganization in the adult neocortex following peripheral injury. The significance of such functional map reorganization, particularly in terms of whether or not cortical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

1990
1990
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Waite and her collaborators (Waite and Taylor, 1978;Waite andCragg, 1979, 1982;Waite, 1984) have used physiological methods to map the representation of the vibrissae follicles in adult rodents after neonatal peripheral damage and showed reductions in the cortical area devoted to the vibrissa pad. While this contrasts with our own results of a lack in reduction of the anatomically defined vibrissa representation after lesions at P-O, it is important to remember that the relationship between anatomical substrate and physiologically defined maps, particularly after peripheral nerve damage, is an imperfect one (see Killackey, 1989, for a discussion of this issue).…”
Section: Discussioncontrasting
confidence: 94%
“…Waite and her collaborators (Waite and Taylor, 1978;Waite andCragg, 1979, 1982;Waite, 1984) have used physiological methods to map the representation of the vibrissae follicles in adult rodents after neonatal peripheral damage and showed reductions in the cortical area devoted to the vibrissa pad. While this contrasts with our own results of a lack in reduction of the anatomically defined vibrissa representation after lesions at P-O, it is important to remember that the relationship between anatomical substrate and physiologically defined maps, particularly after peripheral nerve damage, is an imperfect one (see Killackey, 1989, for a discussion of this issue).…”
Section: Discussioncontrasting
confidence: 94%
“…As a rough metaphor, this would be akin to increasing the volume of a radio, in contrast to frequency-specific changes in RFs, which would be like tuning to another station. 2 Receptive field analysis was first applied to classical conditioning for secondary auditory cortex of the cat and also showed CSspecific plasticity (Diamond & Weinberger 1986, 1989. The emphasis in this article is on primary sensory cortical fields, which constitute all of the other relevant literature.…”
Section: Receptive Field Plasticitymentioning
confidence: 99%
“…The authors also reported novel cutaneous responses in area 3a, interpreted as expanded representation into another cytoarchitectonic area that normally represents only noncutaneous afferentation. However, Killackey (1989) has argued that these findings probably represent the engagement of muscle spindles or the unmasking of weak cutaneous inputs to area 3a rather than an expansion of area 3b. Recanzone et al (1992a,c,d,e) determined the effects of instrumental conditioning of owl monkeys to discriminate between two frequencies of tactile stimulation applied to a small region of a single phalange of a digit.…”
Section: Representational Mapsmentioning
confidence: 99%
“…Cortical representations of sensory surfaces reorganize after partial peripheral deactivations so that at least some of the deprived cortex comes to be activated by inputs from skin regions near the deactivated zone (reviewed by Killackey, 1989;Calford and Tweedale, 1990;Kaas, 1991;O'Leary et al, 1994;Weinberger, 1995). The extent of the reorganization in primates typically is small and can be accounted for by the strengthening of existing but previously subthreshold, or "ineffective," synaptic connections (reviewed by Garraghty and Kaas, 1992).…”
mentioning
confidence: 99%